Development of an Integrated IoT-Based Sanitation System for Air Conditioning Split Units - Izam, Muhammad Nabihan; RAZALI, NIZAMUDDIN; Yunus , Faizal Amin Nur; RAHIM, MOHD BEKRI; KASIMAN, ABD RAHIM (Research and Innovation in Technical and Vocational Education and Training, 2024)
The COVID-19 pandemic underscored the critical importance of effective sanitation methods, particularly in indoor environments where air quality and ventilation significantly influence viral transmission risks. This study introduces an innovative Integrated IoT-Based Sanitation System for Air Conditioning Split Units designed to enhance indoor air quality and reduce the transmission risk of airborne diseases, including COVID-19. The system automates sanitation by leveraging Internet of Things (IoT) technology, utilising real-time environmental data to optimise disinfection protocols. The system was conceptualised, designed, developed, and evaluated through a rigorous research methodology encompassing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and quantitative analysis for efficiency, safety, and user satisfaction. Key findings demonstrate the system's effectiveness in distributing sanitising agents through split unit air conditioning systems, significantly improving indoor air quality. The IoT-enabled features allow for remote monitoring and control, ensuring precise and timely activation of the sanitation process. Through expert analysis and Content Validity Index (CVI) methods, the evaluation revealed strong consensus on the system's design quality, functional efficacy, and potential for widespread application in various indoor settings. Despite the positive feedback, minor areas for improvement in design neatness and component arrangement were identified, offering directions for future enhancements. Integrating IoT technology with air sanitation significantly advances public health measures, providing a novel approach to mitigating airborne transmission risks in enclosed spaces. The system's scalability and adaptability underscore its potential in addressing current and future health challenges, positioning it as a crucial tool in the ongoing fight against airborne diseases.